Workshop report: Playing out transformative adaptation in Usambara, Tanzania - Twyman, Jennifer; Eitzinger, Anton; Shikuku, Kelvin Mashisia; Winowiecki, Leigh Ann; Läderach, Peter R.D.; Koningstein, Manon (2012)
This report documents the information collected during the participatory workshop hosted by The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in partnership with the Selian Agricultural Research Institute (SARI) and Lushoto District Office in the CCAFS site of Usambara Tanzania. This workshop was conducted as part of the CCAFS project “Playing out transformative adaptation in CCAFS benchmark sites in East-Africa: ‘When, where, how and with whom?’ which seeks to identify and understand, through integrated agricultural research, the adaptation process in the CCAFS benchmark site of Usambara, Tanzania. The workshop included farmers from various villages in the CCAFS site, who discussed agricultural practices and perceptions of climate change/variability. The workshop started off with an introduction/icebreaker, after which historical calendars, a discussion of crop suitability and baseline data and gender questions followed. Finally a vision for the future was made, in which the groups were asked to say what they would like to see in the future concerning climate change, food security and gender. The introduction/icebreaker and the general presentation of results were done in a large group but smaller groups were formed to do the historical calendars and to discuss crop suitability and baseline data as well as the gender questions. Most of the small groups were divided by gender, typically with two men’s groups and two women’s groups. In general it can be stated that the farmer is aware of a changing climate and the (negative) consequences this brings about. Furthermore there are differences in perspectives between men and women on the division of tasks and on the household decisionmaking process. Concerning the vision of the future, many farmers let us know that they would like to see more extended information and capacitation on climate change adaptation and mitigation strategies.